A escolha profissional das camadas pobres do município de Manaus: um estudo sobre sentidos e significados - Silva Júnior, João Raimundo dos Santos (2014)
This work is titled "The Professional Choice of poor of the city of Manaus: a study of meanings and senses" and the interest in this topic came from socioeconomic and educational context experienced by young people in the Amazon capital city marked by social inequality among their distinct social strata. It is this social context that the poor youth realize their occupational choices, mostly without the aid of a working toward this process. The study aimed to understand the meanings about their career choice, made of partial college scholarships (50%) of the University Exchange Program, developed by the city of Manaus. For this, we carried out a field survey, guided by qualitative and epistemology grounded in the perspective of socio-historical psychology. Was used as a tool for gathering information dialogical conversation Rey (2005), with two partial college scholarships (50%) of the above mentioned program. With the completion of the study, it was concluded that these students take a critical occupational choice and very little ideological; naturalize the process of choosing a profession, take as true the prevailing hegemonic liberal ideology and perceive the school as a bridge to the professional and social advancement. From these results we concluded the need to implement a public policy career guidance in schools, neighborhood associations, governmental and non-governmental organizations, in order to provide multiple sites for young people to poor people have the opportunity to think, discuss and reflect on the topic and thus perform more critical choices